2009
DOI: 10.1007/s00216-009-2618-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the magnetic properties of ferritin by AFM imaging with magnetic sample modulation

Abstract: Individual ferritin molecules can be sensitively detected using magnetic sample modulation (MSM) combined with contact mode atomic force microscopy (AFM). To generate an oscillating magnetic field, an alternating current (AC) was applied to a solenoid placed within the base of the AFM sample stage. When a modulated electromagnetic field is applied to samples, ferromagnetic and paramagnetic nanomaterials are induced to vibrate. The flux of the AC electromagnetic field causes the ferritin samples to vibrate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…There maybe three reasons for differences in aggregation structure among the three ferritins treated by different heavy metals. First, the observed aggregate morphology of the three ferritins treated with different heavy metals could be related to the nature of the metal cores, the dependence of ferritin aggregate structure on the nature of the metal core is suggested by our SEM results that obvious differences occurred among the same ferritin treated by different heavy metals and small differences occurred among the three different ferritins treated by the same heavy metals, this phenomenon may be explained by the different binding sites used by ferritins to bind the different heavy metals, for example, Cd 2+ was capable of binding to both the inside and outside of Hferritin, this may be also the reason why the same ferritin has different abilities to enrich different heavy metals; second, ferritin could retain its primary structure after demetalation, but its magnetism and conductivity would be altered, which indicated that different heavy metals in iron core could change the conductivity and magnetism of ferritin, further change the number of aggregation ferritin molecular and the final aggregation structure; last, when ferritins are dried, forces, such as hydrophobic and electrostatic forces, likely pull proteins together into a clustered morphology, usually, the stronger the metal ion hydration was, the greater role it played in promoting ferritin aggregation, resulting in the formation of larger ferritin aggregates . Results from CD data showed that heavy metals can hardly alter the secondary structures of the three ferritins.…”
Section: Discussionmentioning
confidence: 83%
“…There maybe three reasons for differences in aggregation structure among the three ferritins treated by different heavy metals. First, the observed aggregate morphology of the three ferritins treated with different heavy metals could be related to the nature of the metal cores, the dependence of ferritin aggregate structure on the nature of the metal core is suggested by our SEM results that obvious differences occurred among the same ferritin treated by different heavy metals and small differences occurred among the three different ferritins treated by the same heavy metals, this phenomenon may be explained by the different binding sites used by ferritins to bind the different heavy metals, for example, Cd 2+ was capable of binding to both the inside and outside of Hferritin, this may be also the reason why the same ferritin has different abilities to enrich different heavy metals; second, ferritin could retain its primary structure after demetalation, but its magnetism and conductivity would be altered, which indicated that different heavy metals in iron core could change the conductivity and magnetism of ferritin, further change the number of aggregation ferritin molecular and the final aggregation structure; last, when ferritins are dried, forces, such as hydrophobic and electrostatic forces, likely pull proteins together into a clustered morphology, usually, the stronger the metal ion hydration was, the greater role it played in promoting ferritin aggregation, resulting in the formation of larger ferritin aggregates . Results from CD data showed that heavy metals can hardly alter the secondary structures of the three ferritins.…”
Section: Discussionmentioning
confidence: 83%
“…To date, decent headway has been made into the application of both AFM and MFM to ferritin detection. Beginning with initial proof-of-concept measurements using AFM, to demonstrate the detection of individual ferritin molecules adsorbed to a surface [119], MFM and bimodal phase imaging have since been used to distinguish between individual apo-and holoferritin, shown in Figure 4 [118]. Detection has also been demonstrated in both air and liquid [118].…”
Section: Ferritin-bound Iron Measurement Techniquesmentioning
confidence: 99%
“…Several patterning techniques have been implemented, such as nanosphere lithography (NSL),145 microlens array (MA) patterning,146 block copolymer (BCP) micelle lithography,147 electron beam lithography (EBL),148 biomimetic layer‐by‐layer assembly (BioLBL),149 and AFM‐based lithographies,150, 151 among others. The great majority of the developed approaches are based on indirect‐patterning deposition techniques, which first fabricate pre‐modified chemical patterns as templates that guide the posterior site‐selective immobilization of the protein onto pre‐defined areas.…”
Section: Use Of Biomolecular Templatesmentioning
confidence: 99%